Enhancing the Predictive Value of SII and NLR in LAA Stroke: Addressing Unexplored Limitations and Future Directions [Response to Letter] - He Z; Liu K (Journal of Inflammation Research)
Zemin He,1 Keting Liu2,3 1Department of Thoracic Surgery, The First People’s Hospital of Shuangliu District (West China Airport Hospital of Sichuan University), Chendu, Sichuan Province, 610200, People’s Republic of China; 2Department of Neurology, Chengdu Seventh People’s Hospital (Affiliated Cancer Hospital of Chengdu Medical College), Chengdu, Sichuan Province, 610213, People’s Republic of China; 3Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong Province, 510515, People’s Republic of ChinaCorrespondence: Keting Liu, Email 921225110@qq.com